Rethinking South Asia: The Bhutanese Refugee Embarrassment - Regmi, Bhim N. (Molung Educational Frontier, 2026)
Nepal and Bhutan, while geographically similar, diverge significantly in their approaches to ethnic inclusion. Bhutan’s transition to parliamentary democracy in 2008 retained exclusionary features, failing to accommodate minority aspirations. Since the early 1990s, approximately 107,000 Nepali-speaking Bhutanese refugees, exiled from Bhutan and demanding Bhutanese citizenship based on historical residence, have spent years in camps in the Terai region of Nepal to resolve their status. Despite repeated bilateral discussions between Nepal and the refugees who expressed their desire to return home, Bhutan did not for Refugees (UNHCR) facilitated this process, with over 91,000 refugees resettled in the United States alone. This article adopts the theoretical framework of Hutt’s ‘Unbecoming the Citizens…’ and Anderson’s ‘Imagined Communities’ to analyze the decade-long displacement of the Lhotshampas, who were denied repatriation. Hutt views that citizenship is not a fixed or secure status for people, and the state can withdraw it at any time. Anderson’s assumption is that nations are constructed communities, and the power of the state can exclude the groups, as the rejection of repatriation remained an unresolved crisis in the Bhutanese case.